Production of silver nanoparticles using yeasts and evaluation of their antifungal activity against phytopathogenic fungi - Fernández, Jorge Gastón (2016)
The present study investigated the biological synthesis, characterization and antifungal activity of silver nanoparticles (Ag NPs). The production of Ag NPs was performed using the culture supernatants of two yeasts: Cryptococcus laurentii and Rhodotorula glutinis. These yeasts were chosen for their nitrate reductase activity. The role of nitrate reductase in the production of nanoparticles was assessed using inhibitors. The characterization of Ag NPs was made by UV-visible spectrophotometry, photon correlation spectroscopy, transmission electron microscopy and X-ray diffraction. Moreover, the FTIR spectrum identified the possible stabilizing agents present in supernatants. The Ag NPs obtained from both yeasts were disperse and stable and exhibited differences in sizes, zeta potential, concentration and stabilizing compounds. The antifungal activity of the Ag NPs was evaluated against the relevant phytopathogenic fungi, the common producers of postharvest diseases in pome fruits. Susceptibility tests on agar demonstrated that the antifungal activity of the nanoparticles from R. glutinis was higher than that from the ones from C. laurentii, and both were significantly more effective for inhibiting the fungi than the nanoparticles made from chemical synthesis. At 3 ppm, the nanoparticles from R. glutinis had similar efficacy to iprodione, a fungicide commonly utilized for combating postharvest diseases.